Palm-Composite: Composite Products From Palm Ash Waste - Ragunathan, Santiagoo; Johnson, Anbu Clemensis, Dr.; Salmah, Hussiensyah, Dr. Ir.; Azlinda, Abdul Ghani; Che Muhd Ruzaidi, Ghazali, Assoc. Prof.; Roshasmawi, Abdul Wahab (AFAG Messen & Ausstellungen GmbH, 2010)
Ragunathan Santiagoo and his team won silver at International Trade Fair for Ideas - Inventions - New Products Exhibition (IENA) 2007 organized by AFAG Messen & Ausstellungen GmbH was held at Nuremberg, Germany on 1st - 4th November 2007.